2018
DOI: 10.1002/jmri.26059
|View full text |Cite
|
Sign up to set email alerts
|

Use of diffusion kurtosis imaging and quantitative dynamic contrast‐enhanced MRI for the differentiation of breast tumors

Abstract: 3 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2018;47:1358-1366.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 27 publications
3
31
1
Order By: Relevance
“…In addition, another study showed that compared with traditional DWI, diffusion kurtosis imaging (DKI) can better distinguish between benign and malignant breast lesions. Also, this article showed that Kep performed better than Ktrans [46]. However, our results suggested that Ktrans value is the best one in predicting prognosis of breast cancer.…”
Section: Discussionmentioning
confidence: 83%
“…In addition, another study showed that compared with traditional DWI, diffusion kurtosis imaging (DKI) can better distinguish between benign and malignant breast lesions. Also, this article showed that Kep performed better than Ktrans [46]. However, our results suggested that Ktrans value is the best one in predicting prognosis of breast cancer.…”
Section: Discussionmentioning
confidence: 83%
“…Further, due to the limited acquisition time, the number of b-values as well as the choice of the highest b value may not be optimal for DKI analysis 36 . For example, in other studies, higher b values and a larger number of them were used 14,16,17 . Nonetheless, the primary objective of this study was to create a shortened DKI protocol applicable in the clinical routine.…”
Section: Discussionmentioning
confidence: 99%
“…While the acquired DWI data is mostly assessed visually in a clinical setting, quantitative multiparametric analysis is gaining increasing attention since it may improve standardization and the still limited specificity of lesion characterization. In this context, diffusion kurtosis imaging (DKI) has been recently introduced in breast DWI analysis yielding a second quantitative parameter, the kurtosis, in addition to the diffusion coefficient [12][13][14][15][16][17][18][19] .…”
Section: Influence Of Residual Fat Signal On Diffusion Kurtosis Mri Omentioning
confidence: 99%
“…For a rigorous estimation, a protocol including at least 15 diffusion weighting directions and 2 non-null b-values would be required [40]. Furthermore, although we applied a high b value of 3000 based on earlier studies utilizing DKI analysis [18,19,41], this does not necessarily suggest that the b values used were optimal for accurate DKI analysis. These factors may have further affected the performance of DKI analysis in our study.…”
Section: Discussionmentioning
confidence: 99%